Synthesis of tetra-substituted metallophthalocyanines: Spectral, structural, computational studies and investigation of their photophysical and photochemical properties - Guzel, Emre; Gunsel, Armagan; Tuzun, Burak; Atmaca, Goknur Yasa; Bilgicli, Ahmet T.; Erdogmus, Ali; Yarasir, M. Nilufer (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This work presents the synthesis of peripherally and non-peripherally tetra-substituted metallophthalocyanines (6-14) containing the 2-(3,4-dimethoxyphenyl)ethanol group. The synthesized compounds were characterized by standard spectroscopy methods. The ligands of the metallophthalocyanines were investigated by quantum chemical calculations. The quantum chemical parameters of these ligands (1 and 2) such as the HOMO, LUMO and chemical hardness were calculated by the B3lyp, HF and M062x methods. The Delta G value of the metal complexes of the ligands were calculated with the obtained results. In addition, photophysical (fluorescence quantum yields) and photochemical (singlet oxygen generation and photodegradation under light irradiation) properties of newly synthesized phthalocyanines were investigated in DMSO solutions, comparatively. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Synthesis; Computational studies; Photosensitizer; Photochemistry; MOLECULAR-DYNAMICS SIMULATION; MICROWAVE-ASSISTED SYNTHESIS; CORROSION-INHIBITORS DFT; LANGMUIR-BLODGETT-FILMS; THEORETICAL EVALUATION; METAL-FREE; BASE-PAIR; PHTHALOCYANINES; DERIVATIVES; WATER; Chemistry; Crystallography